Principles of solar cells, LEDs and diodes : the role of the PN junction - Kitai, Adrian, 1957- (Chichester, West Sussex, U.K. : Wiley, 2011)
"The book will cover the two most important applications of semiconductor diodes - solar cells and LEDs - together with quantitative coverage of the physics of the PN junction at the senior undergraduate level. It will include: Review of semiconductor physics Introduction to PN diodesThe solar cell Physics of efficient conversion of sunlight into electrical energy Semiconductor solar cell materials and device physics Advanced solar cell materials and devices The light emitting diode Physics of efficient conversion of electrical energy into light Semiconductor light emitting diode materials and device physics Advanced light emitting diode materials and devices"--
0
Includes bibliographical references and index.
Keywords: Diodes, Semiconductor; Light emitting diodes; Semiconductors -- Junctions; Solar cells